Mutu Arang Aktif dari Limbah Kayu Mahoni (Swietenia macrophylla King) sebagai Bahan Penjernih Air Quality of Activated Charcoal from Mahogany (Swietenia macrophylla King.) Wood Wastes for Water Purification Substance - Rini Pujiarti; J.P. Gentur Sutapa (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Indonesian active charcoal demands are relatively high, due to the increase of active charcoal usage in industrial sector. To supply active charcoal demand in industrial sector, sufficient amount of basic materials are needed. One of the alternatives is Mahogany wood waste. The aims of this research are (1) to use wood waste of Mahogany (Swietenia macrophylla King.) as a raw material for active charcoal, (2) to identify active charcoal characteristics that are formed, (3) to obtain type and concentration of chemical substance that is suitable for active charcoal forming process, (4) to provide better characteristics, and (5) to apply in the best active charcoal on well-water purification to bind kation in order to increase water quality.Activation was conducted chemically and the types of chemical substance for activation were Na2CO3 and NaOH with concentration of 1%; 1.5%; 2%; 2.5% and 3%. The observed parameters were sucrose contents, moisture contents, volatile matter contents, ash contents, carbon contents, adsorptive capacity of benzene, and adsorptive capacity of iodium and adsorptive capacity of methyline blue.The result and analysis showed that wood waste of Mahogany can be used as a raw material of active charcoal forming process; and Na2CO3 and NaOH can be used as activators. The best active charcoal (with activator Na2CO3 1.5 %) quality was having 64.41% sucrose content, 8.24% moisture content, 3.2% ash content, 19.4% volatile matter content, 77.4% carbon content, 14.48% adsorptive capacity of benzene, 1230.93 mg/g adsorptive capacity of iodium and 130.93 mg/g adsorptive capacity of methyline blue. Well-water quality after the best active charcoal had been added showed decreasing of cation element such as iron (Fe), zinc (Zn) and mangan (Mn